The Use of Video and Multimedia as Learning Evaluation Tools - Nabilla Melani Putri; Septian Khoirul Anam; Desi Susilawati; Ade Tri Mulyani; Muhamad Purwahono Purwahono; Samsilayurni Samsilayurni (DEVOTIONIS, 2026)
The use of learning evaluation instruments is still dominated by written tests, so that students' thinking skills, creativity, and practical skills are not authentically reflected. This problem highlights the need for evaluation media that can record students' processes and performance more comprehensively. This paper aims to describe the use of video and multimedia as learning evaluation instruments. The problem in this study is how to use video and multimedia as learning evaluation instruments. The method used is a literature review, which is based on existing literature and facts in the field. The data or materials obtained are from literature (books, journals, articles, etc.). Data sources were also obtained by collecting literature to obtain theoretical information and explanations. The data analysis technique involved summarizing, presenting data, and providing conclusions. The results of the study show that video can be used to assess student performance in presentations, laboratory practices, motor skills, and collaborative projects, while multimedia provides interactive evaluation support through simulations, digital quizzes, electronic portfolios, and automatic feedback. Both instruments improve the objectivity of assessment, transparency of criteria, and documentation of learning outcomes. In conclusion, the use of video and multimedia is an alternative evaluation instrumen through simulations, digital quizzes, electronic portfolios, and automated feedback. Both instruments enhance the objectivity of assessment, transparency of criteria, and documentation of learning outcomes. In conclusion, the use of video and multimedia is an effective alternative assessment tool in supporting authentic assessment and 21st-century learning, making it worthy of integration into school assessment systems.